Potential of Functionalized-Rice-Husk Ash for Purification of Tannery-yard Liming Effluent: Potential of Functionalized-Rice-Husk Ash for Purification - Abdulla-Al-Mamun, M.; Goush, B. R. (Journal of Scientific Research, 2019)
The natural rise-husk charcoal was made by burned in a furnace at 230 °C. Carboxylic group (-COOH) was functionalized onto the charcoal by using oxalic acid in situ process. Fourier Transform Infrared Spectroscopy (FTIR) and morphology by Scanning Electron Microscope (SEM) demonstrated that the COOH-group was successfully functionalized on the charcoal and the particles were porous. The COOH-activated charcoal was applied for liming effluent treatment through a filtration media. Eight environmental load parameters was determined by the standard method. The results were compared with the standard permissible limits set by Inland Surface Water-Bangladesh Standards (ISW–BDS-ECR, 1997). It has been observed that the rice husk based activated carbons dramatically reduce the pollutants to permissible level. The removal efficiency of pH, Electrical Conductivity (EC), Total Suspended Solids (TSS), Total Dissolved Solids (TDS), Biological Oxygen Demand in 5 days at 20 °C (BOD5), Chemical Oxygen demand (COD), Total Alkalinity, S2- from liming effluent up to 40.0%, 85.89%, 98.8%, 81.32%, 96.74%, 78.6%, 97.15% and 79.61% respectively. In conclusion, the liming effluent simply recycled by filtration process and can be used for industrial purpose.